Physical characteristics of plasma monopole antenna constructed through rf charging of different gases / Nur Aina Halili - Halili, Nur Aina (2015)
Plasma antennas represent the importance of technology in wireless communication that was developed due to its potential and innovativeness. Plasma antenna is a type o f antenna in which the metal conducting elements of a conventional antenna are replaced by plasma. In microwave field, the analyses of different gases by using discharge tube are investigated by injecting the RF source to produce monopole plasma antenna. The discharges have limitation on practical usefulness in commercial applications. This thesis introduces a concept of plasma monopole antennas through RF- charging of different inert gas. The plasma antenna is constructed using different inert gases as the plasma medium. The relationship between the generated plasma parameters and the antenna characteristics are investigated and discussed in two related topics. First, the preliminary studies on plasma antenna performance and behaviour are presented. Special focus is given on proving the theoretical plasma antenna on simulation by using different gas to analyse the characteristics o f plasma antenna behaviour. The antenna’s capability to operate as a transceiver is verified through simulation by using CST Microwave Studio. It is shown that the S- parameter for different gases and pressures give different performance due to the number of turns of coupling sleeve used. The effect of the thickness o f the coupling sleeve is also discussed. The second topic in this thesis is the development of plasma antenna where the implications on the fabricated antenna characteristics are discussed. The antenna characteristics that will be taken into account is the s- parameter, radiation pattern and antenna gain. The capability of plasma antenna is satisfied to transmit and receive the signal when the plasma antenna is supplied with RF sources. This research works are limited to the investigations of basic plasma antenna characteristics in a single antenna setup. Further investigations such as actual implementation of plasma antenna in wireless transmission are also described.